ICT omnipresence and the rights to privacy - Abdulkadir, Abdulkadir Bolaji; Abdulkadir, Abdulrazaq Owolabi (Penerbit Universiti Kebangsaan Malaysia, 2023)
The development of technology and online communication has also led to the appearance of what seem to be certain new types of criminal activity. Cyber security faced difficulties as a result of the rise in criminal behavior and the potential for the creation of new types of criminal activity online. This study evaluates the value of cyber security in an effort to stop cybercrimes based on this assumption. The research methodology used in this work is triangulation, which entails using many approaches to corroborate findings. The goal of this essay is to strike a balance between the requirement for cybersecurity and cybercrimes prevention and the right to privacy.